Enzymatic hydrolysis of bacterial cellulose in the presence of a non‐catalytic cerato‐platanin protein. Issue 14 (8th November 2021) - Rovera, Cesare; Luti, Simone; Pazzagli, Luigia; Heeley, Ellen L.; Wan, Chaoying; Romano, Diego; Farris, Stefano
Abstract: In this work, the effect of an expansin‐like cerato‐platanin (CP) protein as a pre‐treatment for the enzymatic hydrolysis of bacterial cellulose (BC) is investigated. To this scope, cellulases from Trichoderma reesei are used as hydrolyzing agent using different enzyme/BC formulations. Turbidity experiments reveal that for the higher enzyme concentrations (formulations 0.5:1 and 1:1) the enzymatic hydrolysis of BC show similar hydrolysis kinetics and is not dependent of the CP. However, at higher BC concentrations (formulations 0.25:1 and 0.33:1), the hydrolysis of BC is hindered by the non‐catalytic protein, as confirmed by the lower content of cellobiose and glucose in the presence of CP. Light scattering experiments show that the addition of CP led to an increase of the BC particle size from (445–630 nm) to (890–1.26 μm) for the formulation 1:1, which is also corroborated by atomic force microscopy and transmission electron microscopy analyses. These results suggest that CP did not positively affect the hydrolysis of BC, in contrast to what was previously observed for plant‐derived cellulose. This work for the first time investigates the anomalous behavior of cerato platanin family members with regard to its loosening activity on the structure of bacterial cellulose. Abstract :